THE EFFECT OF GOOD CORPORATE GOVERNANCE AND PROFITABILITY ON EARNINGS MANAGEMENT - Nelson Deral Teddy Antou; Nikita JV Poluan; Lanemey Brigitha Pandeirot; Andrew Christian Aseng (Klabat Journal of Management, 2021)
This research aims to determine whether corporate governance has an influence on earnings management. Good Corporate Governance in this research is proxied by using the size of the board of commissioners, independent commissioners, and audit committee. Profitability is proxied by using ROA and ROE. This research uses descriptive statistical method on 102 manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period. It is found that Good Corporate Governance and profitability do not simultaneously affect earnings management. Partially, the board of commissioners, the independent board of commissioners, audit committee, ROA, and ROE, as well as company size as control variables have no significant effect on earnings management. Keywords: Good Corporate Governance, profitability, earnings management